MusaNAC29-like transcription factor improves stress tolerance through modulation of phytohormone content and expression of stress responsive genes - Negi, Sanjana (Plant science : an international journal of experimental plant biology, 2023)
Copyright © 2022 Elsevier B.V. All rights reserved.